De la logique institutionnelle à la connectivité performative : étude thématique des messages publiés sur les sites web du gouvernement fédéral canadien - Ivan E. Ivanov (Communiquer)
This research focuses on the study of the institutional logic and performed connectivity conveyed by official messages of the Canadian federal institutions (CFI) on their official websites through lenses of organizational communication approach (CCO). Since 2015, the Canadian federal government established a new digital communication policy in order to take into account the interactivity and active involvement of individuals and publics as they are increasingly using these digital platforms to communicate with institutions. Our thematic analysis of messages published on CFI websites highlights the dominant traditional and neo-institutional logic of IFC, which obscures human visibility, disincarnates organization and fails to apply the principle of performed connectivity pursued by the official federal communication policy and guideline.